Intussusception Cases Among Children Admitted to Referral Hospitals in Kenya, 2002–2013: Implications for Monitoring Postlicensure Safety of Rotavirus Vaccines in Africa. (25th August 2015) - Omore, Richard; Osawa, Francis; Musia, Janet; Rha, Brian; Ismail, Amina; Kiulia, Nicholas Mukaria; Moke, Fenny; Vulule, John; Wainaina, Anthony Mungai; Tole, John; Machoki, Stanley Mugambi; Nuorti, J. Pekka; et al.
Abstract: To describe the epidemiology of intussusception before introduction of the rotavirus vaccine, we reviewed the records of 280 patients younger than 5 years who were hospitalized in Kenya between 2002 and 2013. The patients who died (18 [6.4%]) had sought care later after symptom onset than the patients who survived (median, 5 vs 3 days, respectively; P = .04). Seeking prompt care may improve therapeutic outcomes.